Spine and Spinal Cord Injuries on the Basis of Medical Documentation - Joanna Rosińczuk; Paweł Pietralik; Łukasz Wojciechowicz; Aleksandra Kołtuniuk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The progressive mechanisation of work in every area of life and the rapid development of means of transport have a major impact on the steadily increasing number of injuries. Spinal injuries are a major medical problem due to the complex structure of the spine, and particularly the neural elements located in the spine. Aim. The analysis of causes, the number and type of injuries of the spine and spinal cord trauma performed on the basis of the documentation from the Emergency Department (ED) of Lower Silesia Specialized Hospitalname Tadeusz Marciniak in Wroclaw and documentation from the Clinic and the University Clinical Hospital (UCH) in Wroclaw. Material and Methods. A retrospective analysis was performed on the documentation of 530 patients from the ED at Lower Silesia Specialized Hospital name Tadeusz Marciniak in Wroclaw who suffered a back injury and/or spinal cord injury and 45 patients from the Clinic and the Department of Neurosurgery at UCH in Wroclaw who were treated for a spine injury and spinal cord injury. Results. The analysis of the study material shows that: — more than a half of the ED patients (58.87%) and 44% of those hospitalized in the Department of Neurosurgery suffered a spinal injury during a traffic collision; — more men were patients in the Department of Neurosurgery (60%), whereas among the ED patients women were slightly more often hospitalized because of a spine injury (52.64%); — the vast majority of respondents with spinal injury were brought to hospital by emergency teams. Conclusions. 1. The predominant reason for spinal injuries and spinal cord injuries being motor vehicle accidents. 2. Mainly young people aged 20–35 years suffer spine and spinal cord injuries. 3. Spine injury most often refers to the cervical part of the spine. (JNNN 2014;3(4):153–156)